Identifying the critical paths and sectors for carbon transfers driven by global consumption in 2015. (15th January 2022) - Xu, Dongxiao; Zhang, Yan; Chen, Bin; Bai, Junhong; Liu, Gengyuan; Zhang, Boyu
Highlights: We developed a sectoral importance indicator to identify key sectors. The first 4 tiers dominated the embodied carbon emission (>70%) at multiple scales. Most transfer paths in USA end in Service, while they in China end in Construction. China's and the USA's Elec-Gas-Water was key primary and final production sectors. China's Petrochemical sector was both a key primary and reprocessing sector. Abstract: Climate change caused by carbon emission threatens human well-being, and global trade drives the transfer of carbon emission between consumers and producers. Thus, quantifying global carbon transfer paths is important. Based on multi-regional input–output tables, we used structural path analysis to decompose the carbon emission processes embodied in trade to analyze the tier structure at multiple scales, and traced critical carbon transfer paths to dissect their distributions. We developed a sectoral importance indicator to consider both the amount of carbon transfer and frequency of sectors to identify key sectors. The first four tiers dominated the embodied carbon emission (>70%) at global, national, sectoral, and national-sectoral scales. Among the critical paths, basic industries (Electricity, Gas, and Water; Petroleum, Chemical and Non-Metallic Mineral Products; Transport), Construction and Services were responsible for the most embodied carbon emission, with the former having prominent direct emission, and the latter sectors having prominent carbon transfers from upstream sectors. The Construction and Electrical and Machinery in China and Services in the United States were key final production sectors; Electricity, Gas, and Water in China and the United States were key primary and final production sectors, and Petroleum and Chemical and Non-Metallic Mineral Products in China was a key primary production and reprocessing sector. Identification of key paths and sectors provides scientific guidance for formulating and adjusting global emission reduction policies.